ENTRE HAMBURGO E RECIFE: UMA SAUDADE E UM BLUES - Soares de Oliveira, Valdevino (Miscelânea: Revista de Literatura e Vida Social, 2017)
Resenha: AZEVEDO, Carlos Alberto. Hamburgo Blues. Belo Horizonte, Maza Edições, 1994.